How Do Acquired Political Identities Influence Our Neural Processing toward Others within the Context of a Trust Game? - Wu, Chien-Te; Fan, Yang-Teng; Du, Ye-Rong; Yang, Tien-Tun; Liu, Ho-Ling; Yen, Nai-Shing; Chen, Shu-Heng; Hsung, Ray-May (Frontiers in Human Neuroscience, 2018)
Trust is essential for mutually beneficial human interactions in economic exchange and politics and people’s social identities notably have dramatic effects on trust behaviors toward others. Previous literature concerning social identities generally suggests that people tend to show in-group favoritism toward members who share the same identity. However, how our brains process signals of identity while facing uncertain situations in interpersonal interactions remains largely unclear. To address this issue, we performed an fMRI experiment with 54 healthy adults who belonged to two identity groups of opposing political orientations. The identity information of participants was extracted from a large-scale social survey on the 2012 Taiwan presidential election. Accordingly, participants were categorized as either the Kuomintang [KMT] or the Democratic Progressive Party [DPP] supporters. During the experiment, participants played trust games with computer agents with labels of the same or the opposing political identity. Interestingly, our results suggest that the behaviors of the two groups cannot be equally attributed to in-group favoritism. Behaviorally, only the DPP supporter group showed a significant trust preference toward in-group members, which did not hold for the KMT supporter group. Consistently, neurophysiological findings further revealed that only the DPP supporter group showed neuronal responses to both unexpected negative feedback from in-group members in anterior insula, temporoparietal junction, and dorsal lateral prefrontal cortex, as well as to unexpected rewards from out-group members in caudate. These findings therefore suggest that acquired identities play a more complex role in modulating people’s social expectation in interpersonal trust behaviors under identity-relevant contexts.